2010
DOI: 10.1503/cmaj.090517
|View full text |Cite
|
Sign up to set email alerts
|

Smarter inspection will improve food safety in Canada

Abstract: Key points• The Canadian food safety system is reactive, and its development has not kept pace with new knowledge used by other countries to protect consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…The generalizability of these findings is not known; while the inspection protocols in the study region are similar to many public health jurisdictions, challenges in transferability related to contextual differences have been noted in previous literature, and it has been postulated that the optimal frequency of inspections may vary by locality. 2,5,11 A review by the National Collaborating Centre for Environmental Health has suggested that optimal frequency and scope of inspections may be jurisdiction-specific. Total (intervention + control groups)x = 0.49 (SD = 0.14)x = 0.27 (SD = 0.26) t = −36.6 (p < 0.001)* * Indicates statistically significant difference (p < 0.05).…”
Section: Restaurant Inspection Frequencymentioning
confidence: 99%
“…The generalizability of these findings is not known; while the inspection protocols in the study region are similar to many public health jurisdictions, challenges in transferability related to contextual differences have been noted in previous literature, and it has been postulated that the optimal frequency of inspections may vary by locality. 2,5,11 A review by the National Collaborating Centre for Environmental Health has suggested that optimal frequency and scope of inspections may be jurisdiction-specific. Total (intervention + control groups)x = 0.49 (SD = 0.14)x = 0.27 (SD = 0.26) t = −36.6 (p < 0.001)* * Indicates statistically significant difference (p < 0.05).…”
Section: Restaurant Inspection Frequencymentioning
confidence: 99%
“…These countries often improve their detection capabilities by increasing the degree of automation and by increasing the number of instruments and equipment. Test scale: Fresno in the California Department of Agriculture analysis of quality inspection agencies less than 50 employees, but there are nine gas chromatographs, not only the detection of these devices ability, but also to ensure the stability of its performance, Tens of thousands of samples from all over the country are tested every year [11]. High test accuracy: The inspection accuracy of EU inspection agencies is also very high.…”
Section: Domestic and Foreign Agricultural Products Quality And Safetmentioning
confidence: 99%
“…Furthermore, food-borne illnesses represent a substantial health and economic burden to Canada, at an average cost of $1089 per case. 4 Our lacklustre effort at detecting, controlling and reporting infections caused by food is problematic. When contaminations are confirmed, we are often unable to trace the origins of the contamination along the food chain.…”
mentioning
confidence: 99%
“…When contaminations are confirmed, we are often unable to trace the origins of the contamination along the food chain. 4 What we need are more active forms of surveillance using common high standards for sampling foods throughout the food chain, for laboratory processing, for rapid removal of foods not meeting the standards and for reporting of laboratory results to the public. For the frail elderly and chronically ill, known high-risk microbes like Listeria are especially problematic -we should aim specifically at zero tolerance for ready-to-eat foods for this population.…”
mentioning
confidence: 99%
See 1 more Smart Citation